Cost-effectiveness and equitable access to vaccines in Ethiopia: an overview and evidence synthesis of the published literature - Solomon T Memirie; Mulat Nigus; Stéphane Verguet (Inishmore Laser Scientific Publishing Ltd, 2021)
In Ethiopia, despite the introduction of new vaccines and a steady increase in access to immunization services over the last decade, considerable coverage gaps have persisted leading to a heavier vaccine-preventable disease (VPD) burden among poorer households. In this paper, we present a brief overview including available evidence and published studies on vaccine economics in Ethiopia, covering the topics of cost-effectiveness analysis, cost of illness associated with VPDs, equitable access to vaccines, and immunization financing. We can then point that large disparities in vaccine access exist by geographic location, socioeconomic and maternal educational status. Ethiopian households, especially the poorest, can incur impoverishing out-of-pocket expenditures for VPDs. Financing for immunization services has shown modest improvements in Ethiopia over recent years prior to the COVID-19 pandemic. A number of economic evaluation studies have pointed to the potentially pro-poor benefits of immunization programs in Ethiopia, yielding health and financial risk protection gains among the poorest households.